Suppression of secondary hyperparathyroidism in children with chronic renal failure by high dose phosphate binders: calcium carbonate versus aluminium hydroxide. Issue 6496 (7th September 1985) - Mak, R H; Turner, C; Thompson, T; Powell, H; Haycock, G B; Chantler, C
Abstract : Secondary hyperparathyroidism was suppressed over a period of one year in 12 children with chronic renal failure by using a regimen of mild dietary phosphate restriction and high dose phosphate binders. The patients were randomised to receive either aluminium hydroxide or calcium carbonate by mouth for six months and then crossed over to the other medication. Vitamin D (dihydrotachysterol) dosage was unchanged. Serum parathyroid hormone concentrations were reduced to within the normal range, urinary cyclic adenosine monophosphate values fell, plasma phosphate concentrations decreased, and the theoretical renal phosphate threshold increased significantly. Transiliac bone biopsy findings improved in four patients with adequate suppression of parathyroid hormone concentrations, deteriorated in two patients who were not compliant, and did not change in five patients in whom initial bone disease was mild. Growth velocity improved significantly. There was no difference in the clinical response, biochemical changes, or incidence of complications during treatment with the two agents. In view of the risk of aluminium toxicity the use of high dose calcium carbonate with dietary phosphate restriction and vitamin D supplementation is recommended in the control of secondary hyperparathyroidism in children with chronic renal failure.